Characteristics Related to Parent-Child Literacy and Numeracy Practices in Preschool - Napoli, Amy R.; Korucu, Irem; Lin, Joyce; Schmitt, Sara A.; Purpura, David J. (Frontiers in Education, 2021)
Despite evidence suggesting that home literacy and numeracy environments are related to children’s school readiness skills, little research has examined the child and family characteristics that relate to the home literacy and numeracy environments within the same sample. These factors are important to investigate in order to determine what may foster or prevent parent-child engagement. The primary purpose of this study was to examine the shared and unique parent-reported child and parent variables that are related to the frequency of parent-child literacy and numeracy practices. The 199 preschoolers included in the study ranged in age from 3.00 to 5.17°years (M = 4.16, SD = 0.57). Parents reported on child and family characteristics. Two multiple regression analyses were conducted (one each for home literacy and numeracy environments). Results indicated that parent education and children’s age were positively related to the frequency of both literacy and numeracy practices. However, parents’ beliefs of the importance of numeracy were positively associated with the frequency of parent-reported numeracy practices, whereas beliefs of the importance of literacy were not related to the frequency of literacy practices. In line with other research, parents reported finding literacy development to be more important than numeracy development and engaging in parent-child literacy practices more frequently than numeracy practices. Understanding factors that are related to the home literacy and numeracy environments may be an important step in identifying how to best encourage parents to engage their children in these practices at home.